Chế tạo màng mỏng oxit niken bằng phương pháp sol-gel trên nền titan kim loại và một số yếu tố ảnh hưởng đến tính chất điện hóa của màng trong dung dịch KOH 1 M - Sén, Trịnh Xuân; Hùng, Phạm Đức (Vietnam Journal of Chemistry, 2014)
In this paper, nickel oxide thin films on the titanium substrate were prepared by the sol-gel dip-coating technique with the precursors NiSO4.7H2O and acetic acid. The obtained thin films have a good adhesion to the substrate. The electrochemical behaviors of the NiOxHythin films were investigated in KOH 1 M solution by the voltammetry technique. The effect of addition of platinum, heating temperature and the dip coating number on the electrochemical behavior was also investigated. The thin films have high electrochemical properties at 270oC and at third dip coating